2002
DOI: 10.1016/s0895-7061(02)02971-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic imidazoline receptor activation in spontaneously hypertensive rats1

Abstract: ANP and BNP may be involved in the antihypertensive effect of chronic moxonidine treatment. Accordingly, natriuretic peptides may contribute to the sympatholytic and cardioprotective effects of chronic activation of imidazoline I1-receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Cardiac I 1 -receptor normalization occurred after 1 week of treatment, the time point when moxonidine resulted in reversal of left ventricular hypertrophy in these rats (Menaouar et al, 2002). Also, the presence of I 1 -receptors in atria, tissues known to secrete or respond to natriuretic peptides, atrial natriuretic peptide and brain natriuretic peptide, suggest a functional relationship between the two systems.…”
Section: Cardiac Imidazoline I 1 Receptors In Shr 449mentioning
confidence: 77%
See 3 more Smart Citations
“…Cardiac I 1 -receptor normalization occurred after 1 week of treatment, the time point when moxonidine resulted in reversal of left ventricular hypertrophy in these rats (Menaouar et al, 2002). Also, the presence of I 1 -receptors in atria, tissues known to secrete or respond to natriuretic peptides, atrial natriuretic peptide and brain natriuretic peptide, suggest a functional relationship between the two systems.…”
Section: Cardiac Imidazoline I 1 Receptors In Shr 449mentioning
confidence: 77%
“…Treatment with moxonidine inhibits or counteracts these effects and eventually may indirectly lead to downregulation of its receptor. We have previously shown that moxonidine dose dependently reduced blood pressure in SHR (Menaouar et al, 2002). However, the dose of 10 g of moxonidine, which had no effect on blood pressure in those rats (Menaouar et al, 2002), significantly reduced I 1 -receptor protein and B max .…”
Section: Cardiac Imidazoline I 1 Receptors In Shr 449mentioning
confidence: 84%
See 2 more Smart Citations
“…Also, in these hearts, moxonidine decreased elevated interleukin 1ß levels (ELISA Kit, Biosource International Inc., Camarillo, CA, USA) in left ventricles from 166 ± 4 to 119 ± 11 pg/ mg protein (P < 0.01) (Figure 4). Most im-portantly, the effects were associated with increased atrial synthesis and release of natriuretic peptides, ANP and BNP ( Figure 5), after 1 week, and normalization by 4 weeks of treatment (34,35). Since natriuretic peptides and their receptors are present in the heart, we propose that moxonidine-stimulated ANP may act in a paracrine/autocrine manner to oppose the inflammatory and hypertrophic effect of overactive SNS and hypertension-associated cardiovascular environment.…”
Section: Imidazoline and Natriuretic Peptidesmentioning
confidence: 90%